OCTODONTOBRADYINAE, UMA NOVA SUBFAMÍLIA DE OROPHODONTIDAE (EDENTATA, TARDIGRADA) DO MIOCENO SUPERIOR-PLIOCENO DO ESTADO DO AMAZONAS, BRASIL (Ameghiniana, 2013)
OCTODONTOBRADYINAE, A NEW SUBFAMILY OF OROPHODONTIDAE (EDENTATA, TARDIGRADA). LATE MIOCENE-PLIOCENE OF AMAZONAS STATE, BRAZIL. A new subfamily of Orophodontidae (Octodontobradyinae), based on one species, Octodontobradys puruensis gen. et sp. n., is described. All the remains, a fragment of the skull and an almost complete mandible, were recovered from the Solimócs Formation of late Miocene-Pliocene (Huayquerian-Montehermosan) age, in the State of Amazonas, Brazil. On the basis of dental histological structure, this new Tardigrada is related to Orophodon hapaloides Ameghino, 1895 and Octodontotherium grandae Ameghino, 1895 of the Oligocene (Deseadan) of Argentina.